A scientist in the field of electrical engineering - Professor V.L. Benin (on the 100th anniversary of birth) - O. V. Lavrinenko (History of science and technology, 2018)
The work is devoted to the study of life, scientific, methodological and educational activities of the professor of the Kharkov Polytechnic Institute Volodymyr Lvovych Benin. In preparing the article, historical and biographical methods were applied, in order to gradually review the stages of life and evaluate the results of a scientist's activity. Нistoriographical analysis of publications V.L. Benin in the context of the dynamics of his scientific work also was made.The analysis of sources and the used archival materials made it possible to objectively evaluate the contribution of the scientist to the development of the industry of automatic regulation, control and statistical power conversion of large power plants, the creation of new measurement circuits and devices while regulating the rotation speed of hydroelectric turbines. It is shown that in the first post-war years his work under the direction of Professor A.L. Matvieiev in the Kharkov electrical laboratory, which at that time was a part of the Institute of Electrical Engineering of the Ukrainian Academy of Sciences, was of great importance for the restoration of the country's energy potential and led to a few technological developments in the energy industry. The result of this work was the defense of V.L. Benin's dissertation under the guidance of an outstanding scientist and innovator S. О. Lebediev. The further scientific activities of V.L. Benin is already in KPI, first of all, as an associate professor of the department of power stations, and then as the head of several important topics and developments in the field of diagnostics and control of diesel generator sets, already at the stage of working on a doctoral dissertation. The talent of V.L. Benin as a teacher and leader, on the example of his students and colleagues, who continued their research, started under his leadership. In the status of the head of the department of theoretical framework of electrical engineering, ethodical and pedagogical contribution of Volodymyr Lvovych in the development and formation of basic discipline for all electrical specialties KhPI was reviewed. His many years of teaching experience allowed him to gradually develop this course, improve certain chapter, supplement individual tasks and expand the laboratory practice of the department. It has also been established that thanks to the many years of hard work by V.L. Benin as a part of the scientific and methodical commission of the Ministry of Higher Education of the USSR, since 1975, the department of TFEE of KPI has become the main department of the Kharkov University Center of theoretical electrical engineering